Property unit trusts in Malaysia - a comparative study / Sarina Said - Said, Sarina (1990)
The scope of this study covers only the three property trusts operating at the point of writing, i.e. FMPT, AMFPT and AHP. This study examines property trusts principally from the point of view of the investor. Accordingly, it does not cover other aspects such as the legal framework and tax ramnifications.